Pain Complaints of Patients Attending Oral Medicine Clinic (Mustansiria Dental Journal, 2018)
A survey was done among (460) patients attending Oral Medicine Clinic with an age (6-75) years. The most common type of pain complaints was orofacial pain (87.8%). This study had been performed to investigate the various type of orofacial pain complaints in (404) patients attending Oral Medicine Clinic.It was found that most common type of orofacial pain complaints was dental pain, pain and swelling (85%) followed by pain/ restricted mouth opening, clicking, fatigue in masticatory system which was recorded (9.4%) of orofacial pain complainers with skewed sex distribution for female.Burning mouth compliant was reported in (5.4%) of orofacial pain complainers with skewed sex distribution for male.Patients accuracy in identifying source of pain was found in 100% patient with burning mouth complaints where as (86.8%) of patients with TMJ. Complain have a real problems in their. Masticatory system of those patients with dental pain. Pain and swelling (79.6%) have a real problem in their teeth or in their periodontium